2019
DOI: 10.1161/hypertensionaha.119.12756
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Wave Velocities Derived From Cuff Ambulatory Pulse Wave Analysis

Abstract: Pulse wave velocity (PWV), a measure of arterial stiffness, is an independent risk factor for cardiovascular morbidity and mortality. We investigated the relationship of ambulatory brachial cuff-based oscillometric PWV (oPWV) to two known correlates: age and brachial systolic blood pressure (SBP).In 234 participants in the Masked Hypertension Study, we analyzed 7,284 validated hourly ambulatory SBP and oPWV readings using the Mobil-O-Graph monitor, which employs a proprietary pulse wave analysis (PWA) algorith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 41 publications
5
43
0
Order By: Relevance
“…Recently, criticism of cuff-based, or algorithm-based devices like the Mobil-O-Graph, which has been used in this study, has been expressed. It is being criticized that the estimation of PWV is largely dependent on age and blood pressure, thus arguably providing no extra information 62 , 63 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, criticism of cuff-based, or algorithm-based devices like the Mobil-O-Graph, which has been used in this study, has been expressed. It is being criticized that the estimation of PWV is largely dependent on age and blood pressure, thus arguably providing no extra information 62 , 63 .…”
Section: Discussionmentioning
confidence: 99%
“…We are aware that the SphygmoCor and Mobil‐O‐Graph use different methods of measuring arterial stiffness. Furthermore, since the planning and conclusion of our study new data have raised questions regarding the technology of PWV measurements by the Mobil‐O‐Graph and whether the PWV measurements are independent of BP and age (Schwartz et al, ). It could therefore be argued that the results cannot be compared.…”
Section: Discussionmentioning
confidence: 99%
“…Any change in PWV after short‐term treatment is therefore more likely to be caused by a decrease in these parameters, rather than any change in the morphology of the arterial wall. Arterial stiffness and BP are strongly related (Schwartz, Feig, & Izzo, ). In our study, we found a significant decrease in office BP as well as in office PWV measured with the Mobil‐O‐Graph.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation could be a high impact of age in the determination of the eaPWV in the algorithm. Recently, the clinical relevance of the eaPWV beyond the impact of age and SBP has been questioned ( Schwartz et al, 2019 ). Despite the known shot-cuts of the oszillometric PWV estimation this method is valid, feasible and easy to apply in the clinical practice.…”
Section: Discussionmentioning
confidence: 99%